2022
DOI: 10.5194/acp-22-5265-2022
|View full text |Cite
|
Sign up to set email alerts
|

Two-way coupled meteorology and air quality models in Asia: a systematic review and meta-analysis of impacts of aerosol feedbacks on meteorology and air quality

Abstract: Abstract. Atmospheric aerosols can exert an influence on meteorology and air quality through aerosol–radiation interaction (ARI) and aerosol–cloud interaction (ACI), and this two-way feedback has been studied by applying two-way coupled meteorology and air quality models. As one of the regions with the highest aerosol loading in the world, Asia has attracted many researchers to investigate the aerosol effects with several two-way coupled models (WRF-Chem, WRF-CMAQ, GRAPES-CUACE, WRF-NAQPMS, and GATOR-GCMOM) ov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 359 publications
1
6
0
Order By: Relevance
“…We find that the relationship between changes in the sfcWind distribution and global temperature is similar to that derived from the idealized 1pctCO2 simulation (Figures S5 and S10 in Supporting Information S1). In contrast, we find that the response of INV is much stronger (Figures S7 and S11 in Supporting Information S1), consistent with previous studies (Gao et al, 2022;Hingmire et al, 2021;Ramanathan et al, 2005;Yang et al, 2016), which have demonstrated that higher anthropogenic aerosols tend to increase atmospheric stability.…”
Section: Change In Local Meteorology With Climate Change and Implicat...supporting
confidence: 92%
“…We find that the relationship between changes in the sfcWind distribution and global temperature is similar to that derived from the idealized 1pctCO2 simulation (Figures S5 and S10 in Supporting Information S1). In contrast, we find that the response of INV is much stronger (Figures S7 and S11 in Supporting Information S1), consistent with previous studies (Gao et al, 2022;Hingmire et al, 2021;Ramanathan et al, 2005;Yang et al, 2016), which have demonstrated that higher anthropogenic aerosols tend to increase atmospheric stability.…”
Section: Change In Local Meteorology With Climate Change and Implicat...supporting
confidence: 92%
“…Therefore, numerical representations of non-spherical aerosol optical properties need to be implemented in two-way coupled models to reduce uncertainties in the ARI calculations. Previous observational and modeling studies revealed that there are still large uncertainties in the impacts of ACI on cloud and precipitation (Seinfeld et al, 2016;IPCC, 2021;Gao et al, 2022), and more researchers have focused on these gaps and gained some remarkable developments on aerosol water uptake and in-/below-cloud scavenging in recent years (Xu et al, 2019;Brüggemann et al, 2020;Kärcher and Marcolli, 2021;Cantrell et al, 2022;Ryu and Min, 2022;Hogrefe et al, 2023). The latest observational investigations for coefficient modifications and newly developed parameterizations/schemes need to be incorporated into the two-way coupled models, such as WRF-CMAQ, WRF-Chem…”
Section: Discussionmentioning
confidence: 99%
“…Aerosol was proven to have direct effects on radiative forcing by absorbing or scattering radiation and indirect effects by participating in cloud formation (Bond et al 2013, Hong et al 2017, Liu and Matsui 2021. Gao et al (2022) reported anthropogenic aerosols decreased shortwave radiative force at the bottom of the atmosphere by 0.45-140.00 Wm −2 in Asia. Thus, the radiative effect can influence ozone formation via its impact on thermal and photolysis reactions.…”
Section: Aerosol Radiative Effectsmentioning
confidence: 99%